Coming of Age in the Dystopian World of Hunger Games - Málek, Ondřej (Univerzita Pardubice, 2015)
This Master's thesis focuses on the depiction of coming of age in the dystopian world of The Hunger Games. The analysis of the characters is conducted on the basis of the terms utopia, dystopia, anti-utopia, Young Adult literature, and coming of age with the emphasis on the factors influencing their coming of age: the struggle for power, loss of home, and gender issues. On the basis of these findings, the effects and consequences of setting the process of coming of age into the dystopian world are summarized.
Coming of Age in the Dystopian World of Hunger Games
Keywords: dystopie; dospívání; moc; domov; gender; dystopia; coming of age; power; home